DNA barcoding of invasive plants in China: A resource for identifying invasive plants. (4th October 2017) - Xu, Song‐Zhi; Li, Zhen‐Yu; Jin, Xiao‐Hua
Abstract: Invasive plants have aroused attention globally for causing ecological damage and having a negative impact on the economy and human health. However, it can be extremely challenging to rapidly and accurately identify invasive plants based on morphology because they are an assemblage of many different families and many plant materials lack sufficient diagnostic characteristics during border inspections. It is therefore urgent to evaluate candidate loci and build a reliable genetic library to prevent invasive plants from entering China. In this study, five common single markers (ITS, ITS2, matK, rbcL and trnH‐psbA ) were evaluated using 634 species (including 469 invasive plant species in China, 10 new records to China, 16 potentially invasive plant species around the world but not introduced into China yet and 139 plant species native to China) based on three different methods. Our results indicated that ITS2 displayed largest intra‐ and interspecific divergence (1.72% and 91.46%). Based on NJ tree method, ITS2, ITS, matK, rbcL and trnH‐psbA provided 76.84%, 76.5%, 63.21%, 52.86% and 50.68% discrimination rates, respectively. The combination of ITS +  matK performed best and provided 91.03% discriminatory power, followed by ITS2 +  matK (85.78%). For identifying unknown individuals, ITS +  matK had 100% correct identification rate based on our database, followed by ITS/ITS2 (both 93.33%) and ITS2 +  matK (91.67%). Thus, we propose ITS/ITS2 +  matK as the most suitable barcode for invasive plants in China. This study also demonstrated that DNA barcoding is an efficient tool for identifying invasive species.